Nonocclusive Mesenteric Ischemia after Chemotherapy in an Adolescent Patient with a History of Three Allogeneic Hematopoietic Stem Cell Transplantations for Acute Lymphoblastic Leukemia - Koichi Hirabayashi; Mitsuho Takatsuki; Mitsuo Motobayashi; Takashi Kurata; Shoji Saito; Tomonari Shigemura; Yozo Nakazawa; Kazuo Sakashita; Satoshi Ishizone; Hiroyoshi Ota; Kenichi Koike (Elsevier, 2017)
Nonocclusive mesenteric ischemia (NOMI) is induced by intestinal vasospasm without thromboembolic occlusion and is associated with high morbidity and mortality. The estimated overall incidence of autopsy-verified fatal NOMI is 2.0 cases/100,000 person-years; however, no pediatric or adolescent cases have yet been reported. An 18-year-old female was diagnosed with B-cell precursor acute lymphoblastic leukemia at the age of 10 years. Our patient received three allogeneic hematopoietic stem cell transplantations but experienced hematological relapse after each. She received combination therapy of prednisolone, L-asparaginase, vincristine, and bortezomib after the third relapse. On Day 16 after the initiation of chemotherapy, she developed NOMI; therefore, we performed a right-sided hemicolectomy on Day 27. Nonocclusive mesenteric ischemia should be considered during the differential diagnosis of intestinal complications after chemotherapy, even in pediatric and adolescent patients.